The Development of Chinese Artificial Intelligence Science Fiction Movies through the Lens of the Film Industry Chain - Teng, Xu; Desa, Mohd Asyiek Mat (Journal of Cultural Analysis and Social Change, 2025)
Since The Wandering Earth (2019) achieved commercial success, Chinese sci-fi cinema—particularly works centered on artificial intelligence as their core narrative and aesthetic—has entered a new phase of industrial development. This paper does not treat this transformation as a mere genre trend; rather, it examines Chinese AI sci-fi cinema as an emerging industrial form shaped by the interplay of creative labor, production technology, capital structure, institutional governance, and intellectual property (IP) management. Using a film industry value chain analysis framework, this study re-evaluates the structural bottlenecks constraining sustainable development: interdisciplinary talent shortages, technological dependence, high-risk financing mechanisms, inadequate legal protections, and underdeveloped derivative commercialization. This paper situates Chinese AI science fiction films within broader discussions of cultural industrialization and IP-driven growth, emphasizing that the core challenges in this field lie not only in technological limitations but also in the incomplete integration of creativity, technology, and institutional coordination. The conclusion proposes an industry-oriented development pathway, highlighting systematic talent cultivation, collaborative technological advancement, diversified risk-sharing mechanisms, strengthened legal governance, and early-stage IP planning. This approach outlines a localized model for the long-term maturation of China’s sci-fi film industry.